EFFECTS OF GARLIC EXTRACT ON SOME BIOCHEMICAL PARAMETERS OF BLOOD IN MALE ALBINO RATS - SASHANK SRIVASTAVA,; P. H. PATHAK, (The Bioscan, 2010)
The prophylactic efficacy of garlic (Allium sativum Linn) (Alliaceae) extract was studied on some biochemical parameters in male albino rats. The rats were divided into four groups A, B, C and D, keeping group A as a healthy control. The garlic extract was tried in three different doses, 1mL, 2mL and 4mL/ kg body weight as low, medium and high dose respectively and given orally for the period of 7, 14, 21 or 28 days daily to the rats of group B, C and D as stated above. The observation clearly indicates that there was significant decrease (p<0.01) in glucose and cholesterol level at each dose and time period, whereas SGPT and SGOT level decreases significantly (p<0.05 and p<0.01) at low and medium dose at all the periods of treatment, but at higher dose its level increases significantly (p<0.05 and p<0.01) with respect to control. The above study clearly indicates the benefits and drawbacks of raw garlic.